Comparison of different insulin resistance surrogates in predicting hyperuricemia in non-diabetic Yi residents in Yunnan Province - Dao, Mengyao; He, Xianyu; Ji, Yanmei; Guo, Ni; Li, Wenjun; Xiong, Qing; Meng, Ni; Zhou, Dan; Pi, Ting; Zong, Xiaofeng; Yang, Meirong; Liu, Xinyi; et al. (Frontiers in Endocrinology, 2025)
Background and purposeHyperuricemia (HUA) is one of the most common metabolic diseases in China, with an incidence of up to 36% across different ethnic groups. Insulin resistance (IR) plays a specific role in the occurrence and development of HUA, but relevant studies on the non-diabetic Yi residents in Yunnan are limited. Our study aimed to explore the triglyceride-glucose index (TyG), triglyceride-glucose and body mass index (TyG-BMI), triglyceride/high-density lipoprotein cholesterol ratio (TG/HDL-C), and the metabolic score for insulin resistance (METS-IR) among non-diabetic Yi residents in Yunnan Province, and identify the IR surrogates with high predictive ability for HUA.Materials and methodsFrom November 2018 to September 2023, our group finally included 765 Yi residents aged ≥18 years on the basis of the inclusion criteria. The participants were divided into the non-HUA and HUA groups. Logistic regression analysis was used to describe the association between four IR surrogates and HUA and calculate odds ratios (ORs), while the receiver operating characteristic curve was utilized to assess the prediction ability of these four IR surrogates.ResultsAmong the 765 non-diabetic Yi residents in Yunnan, 666 were in the non-HUA group, and 99 were in the HUA group. A history of smoking, alcohol consumption, hypertension, and hyperlipidemia, body mass index (BMI) ≥ 24 kg/m2, triglyceride, serum creatinine levels, TyG, TyG-BMI, TG/HDL-C, and METS-IR were found positively correlated with the occurrence of HUA (P < 0.05). In contrast, in female, HDL-C levels were negatively correlated with the occurrence of HUA (P < 0.05). Logistic regression analysis showed that after adjusting for age, smoking history, alcohol consumption history, history of hyperlipidemia, history of hypertension, systolic and diastolic blood pressures, cholesterol, low-density lipoprotein, serum creatine levels, TyG, TyG-BMI, TG/HDL-C, and METS-IR were found independent influencing factors for the occurrence of HUA. Receiver operating characteristic curve analysis showed that these four IR surrogates had certain predictive ability for HUA.ConclusionThis study found that in non-diabetic Yi residents in six areas of Yunnan Province, the TyG, TyG-BMI, TG/HDL-C, and METS-IR were positively correlated with HUA. These four IR surrogates were good at predicting HUA.